Chronic arsenate exposure affects amphipod size distribution and reproduction - Visviki,Ioanna; Judge,Michael L. (PeerJ, 2020)
Arsenate (As V) is the predominant inorganic species of arsenic in oxic aquatic environments. Chronic water quality criteria for arsenate have not been established due to the scarcity of relevant studies on its impact on aquatic biota. We examined the acute and chronic effects of arsenate on the benthic amphipod Leptocheirus plumulosus, an important test organism for ecotoxicological studies. We determined that a concentration of 1,971 µg/L arsenate induced 50% mortality (LC50) in juveniles in 96-hr water only exposure. Subsequently, we tested the efficacy of a 42-day sediment bioassay to determine chronic population-level effects. Specifically, we analyzed the survivorship, size distribution, reproduction and offspring sex ratio of this amphipod to a sublethal concentration of arsenate. The sublethal concentration was determined based on the results of the acute tests. Arsenate (500 µg/L) was added to seawater (20 psu) overlying natural sediments (particle sizes < 250 µm). Fifteen replicate chambers per treatment were employed, each stocked with 20 stage-sorted juvenile amphipods (500–600 µm). Five replicates per treatment were destructively sampled on week 3 and ten replicates were sampled on week 6. Arsenate exposure did not affect the survivorship of parental amphipods, as expected, but it decreased significantly the number of offspring in the largest size classes. By week 6, arsenate-exposed replicates had statistically fewer sexually mature offspring compared to controls, likely because the overall reproduction was suppressed. Arsenate exposed amphipods had significantly fewer offspring than controls by week 6 (9.3 vs. 19.1 per parent), but the sex ratio of the offspring was not altered. Our results indicate that size distribution and reproduction may be more sensitive endpoints than survivorship for the chronic effects of arsenate in oxic systems. The extended 42-day bioassay with Leptocheirus plumulosus is a very promising tool to study the effects of toxicants on population dynamics.
Keywords: Arsenate; Chronic; Sediment; Amphipods; Leptocheirus; Reproduction; Offspring sex ratio; Cohort maturation; Cohort size distribution